An e-quiz system: A pathway to improve English learning for preschoolers in rural areas / Anis Roslan ... [et al.] - Roslan, Anis; Razak, Tajul Rosli; Ismail, Mohammad Hafiz; Abd Halim, Iman Hazwam (UiTM Cawangan Perlis, 2022)
E-Quiz Systems is a system that replaces manual techniques, which are paperless methods often utilised in rural preschools. This paper presents an interactive web-based solution to assist students and teachers in rural regions with English language learning and instruction. This study attempts to motivate preschoolers in rural locations to learn English while providing instructors with interactive web-based methods to measure their students’ knowledge levels. A web-based application system is created to display e-quiz questions using the interactive multimedia principles of multiple media types and navigation with user input. Using interactive multimedia concepts, an E-Quiz System is designed to serve as an interactive quiz for English learning. ADDIE Model was the approach employed in this project. In addition, this project underwent testing for functionality and usability. As a contribution, it has been established that this study will give a pathway that piques children’s interest in learning English and makes it simpler for instructors to evaluate children’s growth using the E-Quiz System score.